Safety Profile of Anticancer and Immune-Modulating Biotech Drugs Used in a Real World Setting in Campania Region (Italy): BIO-Cam Observational Study - Scavone, Cristina; Sportiello, Liberata; Sullo, Maria G.; Ferrajolo, Carmen; Ruggiero, Rosanna; Sessa, Maurizio; Berrino, Pasquale M.; di Mauro, Gabriella; Berrino, Liberato; Rossi, Francesco; Rafaniello, Concetta; Capuano, Annalisa; et al. (Frontiers in Pharmacology, 2017)
Objectives. To investigate the occurrence of adverse events (AEs) in naïve patients receiving biotech drugs. Design. A prospective observational study. Setting. Onco-hematology, Hepato-gastroenterology, Rheumatology, Dermatology, and Neurology Units in Campania Region (Italy). Participants. 775 patients (53.81% female) with mean age 56.0 (SD 15.2). The mean follow-up/patient was 3.48 (95% confidence interval 3.13 to 3.84). Main outcome measures. We collected all AEs associated to biotech drugs, including serious infections and malignancies. Serious AEs were defined according to the International Conference on Harmonisation of Technical Requirements for Registration of Pharmaceuticals for Human Use, clinical safety data management: definitions and standards for expedited reporting E2A guideline. Results. The majority of the study population was enrolled in Onco-hematology and Rheumatology Units and the most common diagnosis were hematological malignancies, followed by rheumatoid arthritis, colorectal cancer, breast cancer and psoriatic arthritis. The most commonly prescribed biotech drugs were rituximab, bevacizumab, infliximab, trastuzumab, adalimumab and cetuximab. Out of 775 patients, 320 experienced at least one AE. Most of patients experienced AEs to cetuximab therapy, rituximab and trastuzumab. Comparing female and male population, our findings highlighted a statistically significant difference in terms of AEs for adalimumab (35.90% vs 7.41%, p<0.001) and etanercept (27.59% vs 10.00%, p=0.023). Considering all biotech drugs, we observed a peak for all AEs occurrence at follow-up 91-180 days category. Bevacizumab, brentuximab, rituximab, trastuzumab and cetuximab were more commonly associated to serious adverse events; most of these were possibly related to biotech drugs, according to causality assessment. Three cases of serious infections occurred. Conclusions. The results of our study demonstrated that the majority of AEs were not serious and expected. Few cases of serious infections occurred, while no case of malignancy did. Overall, the safety profile of biotech drugs used in our population was similar to those observed in pivotal trials. Notwithstanding the positive results of our study, some safety concerns still remain unresolved. In order to collect more effectiveness and safety data on biotech drugs, the collection and analysis of real world data should be endorsed as well as the management of post-authorization studies.